The Dynamic Innovative Balance System Improves Balance Ability: A Single Blind, Randomized Controlled Study - Bunyamin Haksever; Irem Duzgun; Gul Baltaci (North American Sports Medicine Institute, 2021)
# Background Functional balance training is crucial for both rehabilitation and prevention. A Dynamic Innovative Balance System (DIBA) is readily available for utilization in both functional and postural control training in a wide variety of dynamic conditions. # Purpose The purpose of this study was to compare the effectiveness of the DIBA and standard balance training tools on dynamic and static balance. # Study Design Randomized controlled trial # Methods Thirty-six healthy males (18 to 32 years) were randomly assigned to group DIBA (n=18) or to the control group (n=18) who performed balance training using a balance board, a wobble board, the BOSU, or a soft cushion block for eight weeks. Each participant was assessed before training, at the end of the fourth and eighth week by using the Flamingo balance test (FBT) for assessing static balance ability and using Y-Balance Test (YBT) for dynamic balance ability. # Results No significant differences were found in FBT and YBT between the DIBA and control groups at the end of fourth week (p\>0.05). However, at the end of the eighth week, the DIBA group demonstrated statistically significantly better balance ability on the anterior component of YBT (p=0.001) and FBT (p=0.024) than controls. # Conclusion The results of this study suggest that the DIBA was effective in both static and dynamic balance training and it may be used alongside other balance tools in a clinical setting. Further studies should include in lower extremity problems to confirm that DIBA training adaptations are transferred to clinical improvements in performance and balance qualities. # Level of Evidence 2d